Crashworthiness performance of thin-walled, square tubes with circular hole discontinuities under high-speed impact loading. Issue 6 (2nd November 2022) - Taghipoor, Hossein; Ghiaskar, Ahmad; Shavalipour, Aghil
Abstract: This paper presents an experimental investigation about the effect of the hole on the crushing force of thin tubes with the square cross-section under axial impact with a high strain rate. To this end, 24 absorbers were studied and their crushing properties were extracted and compared with a simple absorber. The effect of different parameters, including hole diameter, sample length, sample cross-section size, and impact speed were also evaluated. It was found that in hole square thin-wall tubes with high strain rates, an increase in tube length did not affect the maximum force. The results showed that considering cylindrical tubes, average and maximum force in square thinwall tubes without a hole are less than those with holes; this difference in force was not significant but collapse force efficiency (CFE) decreased to 46%. Moreover, by the increase of hole diameter, the maximum force to square thin wall decreased.